An ultra-low supply low dropout regulator for internet-of-things applications - Zhang, Xinyan (Nanyang Technological University, 2021)
The trend for electronic products is smaller, more portable, multifunctional, wearable and etc. This requires high performance power management to supply for different modules in the chip precisely. Low drop-out (LDO) regulator plays a significant part of on-chip power management, especially in low voltage and low power design, which can be widely used in the IoT applications. In this work, the design of an output-capacitorless ultra-low supply low dropout LDO regulator is presented in TSMC 40nm CMOS technology. It can operate at 0.6V supply and provide 0.4V dc output voltage with a quiescent current of 18.5μA. Besides, this proposed circuit topology can respond fast to the output load step change from 0 to 25mA with 18mV overshoot and 39mV undershoot. Besides, the simulated line regulation is 1.63μV/mV and load regulation is 0.073mV/mA. The proposed regulator is very useful for IoT applications.